(untitled) (International journal of medical sciences, 2026)
Background: Emergency complications following pediatric cardiac surgery for congenital heart defects (CHD) remain a significant challenge in intensive care management, requiring prompt multivariate assessment of vital parameters. Methods: A prospective observational study included 42 pediatric patients (aged 1 month to 14 years) admitted to the ICE department following cardiac surgery between January 2025 and December 2025. Vital parameters including heart rate, blood pressure, oxygen saturation, respiratory rate, temperature, and vasoactive-inotropic requirements were monitored during the first 48 postoperative hours. Results: Emergency complications occurred in 33.3% (n=14) of patients. Patients with complications demonstrated significantly higher heart rate (145±18 vs. 118±12 bpm, p<0.001), lower mean arterial pressure (52±8 vs. 68±7 mmHg, p<0.001), decreased oxygen saturation (88±6 vs. 96±3%, p<0.001), and elevated respiratory rate (42±9 vs. 28±5 breaths/min, p<0.001) compared to stable patients. Conclusion: Multivariate vital sign monitoring reveals distinct patterns of cardiovascular and respiratory deterioration in pediatric cardiac surgery patients. Early recognition of combined hemodynamic instability enables timely intervention and improved outcomes.